Assessment of Common Problems of Post Graduate Students Pursuing F.C.P.S and M.D.S in Orthodontics and Dentofacial Orthopedics, Due To COVID 19 Lockdown - Erum Behroz; Sarvaich Kumar; Danish Ali Mottani; Hafiz Zuhair Ahmed; Ayesha Bibi`; Sohail Khan (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Abstract Objective: To assess the common concerns of FCPS and MDS trainees in Orthodontics due to COVID-19 lockdown. Methods: This cross-sectional study was conducted in different institutes of Sindh which offered FCPS/MDS training in Orthodontics. The study was carried out after approval from the ethical commit- tee. A questionnaire was designed comprising of 15 questions. Each question aiming to assess the difficulties faced by trainees due to the imposition of lockdown. The questionnaire was distributed amongst 80 participants/trainees in the training year 2 to 4. Results: The average age of study participants was 29 years with range of 27 to 38 years. In this study a large number of subjects said that they were unsure regarding completion of cases due to lockdown i.e; n=63,(77.8%). Approximately half of the study subjects thought that there will be mas- sive patient burden after resuming to the normal practice i.e 40(49.4%). Nearly quarter of them were puzzled that due to lockdown it was difficult to focus on thesis and research work i.e 18(22.2%). Few of them also responded that after resuming to the normal practice there would be pressure from su- perior authorities for academic works i.e; n=9,(11.1%). Conclusion: This study analyzed those major concerns were non-availability of basic materials for procedures, fear of completion of cases due to lockdown and massive patient burden in clinics after uplifting of lockdown. Therefore, Covid-19 lockdown has in many ways affected the academic and clinical activities of the post-graduate students. The uncertainty to tackle this surprise situation is still an unanswered question.